Effect of expansive agent on temperature and deformation of concrete under simulated actual construction condition - Ming Li; Ang Su; Hua Li; Yujiang Wang; Qian Tian (Case Studies in Construction Materials)
Prolonging the setting time of concrete is a common requirement for the construction of massive structural engineering, and the molding temperature of concrete changes greatly with the construction season temperature. These actual construction conditions may bring challenges to the use of expansive agent (EA) to inhibit concrete cracking. This paper aims to investigate the effect of calcium oxide EA (CEA), magnesium oxide EA (MEA), and calcium magnesium composite EA (CMA) on the temperature and deformation of concrete under simulated actual construction condition by concrete member test, and discusses the hydration heat, autogenous shrinkage deformation and mechanical properties of cement-based materials containing EA under standard laboratory condition. Results show that CEA, MEA, and CMA increase the temperature rise of concrete members by 3 °C to 7.8 °C, which is not completely consistent with the hydration heat results under standard condition. For the concrete containing EA under the entity variable temperature, the extension of setting time and the increase of molding temperature reduce the shrinkage compensation ability of EA, the average expansion deformation rate of concrete in the temperature rise stage is reduced, and the average shrinkage deformation rate of concrete in the temperature drop stage is increased. Temperature rising inhibitor (TRI) is recommended to be used together with EA, which can eliminate the adverse effect of EA on the increase of temperature rise, greatly improve the shrinkage compensation ability of EA, and hardly reduce the later strength of concrete.